PENGARUH TIPE HIBRID, BOBOT BENIH, DAN PENUTUPAN MULSA TERHADAP KECEPATAN DAN PERSENTASE DAYA BERKECAMBAH TIGA TIPE KELAPA HIBRID - Maman Herman; Dibyo Pranowo; H. T. Luntungan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1998)
Three types of coconut hybrid, namely Salak Dwarf (SKD) x Tenga Tall (TAT), Salak Dwarf x Sawarna Tall (SAT), and Salak Dwarf x Markamvalley Tall (MVT) were studied in Kotabumi, North Lampung, from July 1994 to March 1995 on Red Yellow Podzolid soil. This trial was conducted to determine the percentage of germination and speed of germination based on hybrid type, seed weight, and mulching. Split-split plot design consisted of three factors with three replications was used for this trial. The first factor as main plot was three levels of hybrid SKD x TAT, SKD x SAT, and SKD x MVT. The second factor as sub plot was three levels of seed weight less 500 g, 501-800 g, and more than 801 g. The third factor as sub-subplot consisting of four levels of mulching 0, 30, 60, and 100 percent. The results showed that SKD x SAT germinated faster than SKD x MVT and SKD x TAT. The germination percentage of SKD x MVT was higher compared to SKD x TAT, but similar to SKD x MVT The germination speed was not affected by seed weight, where the germinating percentage was nuts less than 501 g germinated better than those more than 501 g. Treatment of mulching not significant by influence growth rate of germination but significantly influence the percentage of seednut germination thirty percent of mulching gave the best percentage of seed nut germination.